Effect of Cr on the microstructure and oxidation properties of Co-Al-W superalloys studied by in situ environmental TEM. (December 2019) - Chen, Yanhui; Xue, Fei; Wang, Chunhui; Li, Xueqiao; Deng, Qingsong; Yang, Xiaomeng; Long, Haibo; Li, Wei; Yang, Luyan; Li, Ang
Highlights: Modern in-situ oxidation process down to nanoscale was introduced in a TEM and provide more detailed intrinsic information. Cr addition (0–10 at.%) to γ/γ´ structure Co82 Al9 W9 -based superalloy was systematically investigated by analytical electron microscopy. The in-situ oxidation behavior of Cr contained alloys in an environmental TEM were studied and moderate Cr addition are suggested for alloy design. Abstract: Modern in situ oxidation processes can be observed down to the nanoscale using environmental transmission electron microscope (TEM), and this technology has been applied to conventional corrosion science to provide more detailed intrinsic information on the oxidation properties of materials. The influence of chromium (0–10 at.%) addition on the microstructure and oxidation properties of a γ/γ′ two-phase Co82 Al9 W9 -based superalloy was systematically investigated. The in situ oxidation behaviour of Cr-containing alloys was studied using environmental TEM, and the addition of moderate Cr amounts is suggested for the alloy design.